Analisa Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Ritel Dikabupaten Karanganyar - Rowiyani, Rowiyani; Pamastutiningtyas, Terrensia Sekar; Muslikhun, Alfin; Mukhlidin, Mukhlidin (STIE AMKOP, 2024)
This research aims to analyze the factors that influence the income of retail traders in Karanganyar Regency, namely analysis of business capital, marketing strategies, and entrepreneurial characteristics on the income of retail traders in Karanganyar Regency.. This research uses a quantitative approach with primary data collected through questionnaires. The research sample was selected using a purposive sampling technique, which includes various types of retail businesses in Karanganyar Regency. The data analysis methods used include instrument testing, classical assumption testing, and hypothesis testing using SPSS for Windows. The research results show that business capital, marketing strategies, and entrepreneurial characteristics have a significant positive effect on retail traders' income. The Adjusted R² value of 0.872 shows that the three independent variables are able to explain 87.2% of the variation in retail traders' income, while 12.8% is explained by other factors. Validity and reliability tests show that the instruments used meet the validity and reliability requirements. The classical assumption test also shows that the data used meets the assumptions of normality, there is no multicollinearity, heteroscedasticity and autocorrelation. Based on the results of the analysis, it is recommended that retail traders increase creativity and innovation in entrepreneurial characteristics, as well as optimize business capital and marketing strategies, especially in the use of technology digital. Future research is recommended to take a larger sample and add other independent variables that might influence retail traders' income to obtain more comprehensive results. Keywords: Business Capital, Marketing Strategy, Entrepreneurial Characteristics, Retailer Income